Pelatihan Pengembangan Bahan Ajar dan Modul Ajar untuk Fase F bagi Guru MGMP Bahasa Inggris Jawa Timur: Training on the Development of Teaching Materials and Instructional Modules for Phase F for the East Java English MGMP Teachers - Munir, Ahmad; Aminin, Zainul; Nugroho, Him'mawan Adi; Dari, Retno Wulan; Rahmawati, Eva; Akhiriyah, Suvi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The Senior High School English MGMP of East Java Province faces several urgent issues, including the large number of terminologies and processes that must be internalized and implemented within the Merdeka Curriculum and its supporting components. In addition, the Senior High School English MGMP of East Java Province should specifically focus on developing instructional modules and teaching materials for Senior High School English subjects in the Merdeka Curriculum, particularly for Phase F (General and Advanced). The proposed solution to address these challenges is to provide training on breaking down the Learning Outcomes, Learning Objectives, and Learning Objective Pathways for Phase F General and Phase F Advanced, as well as on developing Phase F Instructional Modules and English teaching materials. This training is conducted through practical workshops. This method is chosen because it aligns with participant-centered principles, is non-directive, and enables teachers to work collaboratively, actively, and productively. The community service activities with the East Java Senior High School English MGMP have been carried out through several stages: coordination meetings with MGMP board members, preparation of training modules, delivery of theoretical materials, preparation of Phase F instructional module materials, offline theoretical sessions, practical workshops on developing teaching materials and instructional modules for both General and Advanced Phase F, and follow-up activities. All activities were successfully implemented, and nearly all expected outputs were achieved.